A new species of Myrceugenia (Myrtaceae) from Southern Brazil - Vieira, Fábio Christiano Speck (Phytotaxa, 2020)
Myrceugenia joinvillensis, a new species from the Brazilian Atlantic Forest is described and compared with related species. This taxon seems to be restricted to the Serra do Mar range in the Southern Brazilian state of Santa Catarina in the municipalities of Joinville and Schroeder. Additionally, there are provided information on its phenology, distribution and conservation status.